Occurrence of perfluorooctanesulfonate and perfluorooctanoic acid and histopathology in eels from north Italian waters. (January 2015) - Giari, Luisa; Guerranti, Cristiana; Perra, Guido; Lanzoni, Mattia; Fano, Elisa Anna; Castaldelli, Giuseppe
Highlights: First study of perfluorinated alkylated substances in fish from the Po River, Italy. Contamination levels in eels comparable to, or lower than, those found in other areas. Wide range of perfluorooctanoic acid concentrations. Highest accumulation in blood, lowest in muscle. Moderate lesions in liver and absence of anomalies in gonad. Abstract: A perfluorinated alkylated substances (PFAS) biomonitoring study was conducted in European eel ( Anguilla anguilla ) in Italy for the first time. Perfluorooctanesulfonate (PFOS) and perfluorooctanoic acid (PFOA) concentrations were assessed in the organs of 35 wild eels from two locations, the highly impacted Po River and the Comacchio Lagoon along the north-western Adriatic coast. PFAS were extracted by ion-pairing liquid extraction procedure and measured using high performance liquid chromatography with electrospray ionization tandem mass spectrometry. There were no significant differences in mean PFAS concentrations ( p > 0.05) between samples from the two sites. PFOS and PFOA were detectable (>0.4 ng g −1 wet weight, w.w) in 73% and 31% of the total samples, respectively. PFOS concentrations ranged from <0.4 to 6.28 ng g −1 w.w and PFOA from <0.4 to 92.77 ng g −1 w.w. The highest PFAS levels were observed in blood and the lowest in muscle. Histology showed macrophage aggregates and hepatocytic vacuolation in some liver samples. No tissue anomalies were seen in the gonads, suggesting no reproductive impairment. The PFAS contamination levels observed were comparable to, or lower than, those reported in fish in other European countries, seeming to indicate that PFAS pollution of the study area is not remarkable.